Membrane Filtration Applied to the Purification of Sugarcane Bagasse Mild Alkaline Extracts - Vincent Oriez; Nga Thi-Thanh Pham; Jérôme Peydecastaing; Philippe Behra; Pierre-Yves Pontalier (Clean Technologies, 2023)
Sugarcane bagasse (SCB), a by-product of the sugar industry, is composed mainly of cellulose, hemicelluloses, and lignin, and can be used to replace petrochemical polymers in various applications. In this work, SCB was treated under mild alkaline conditions with 1.5% NaOH (m:v) and a solid:liquid ratio of 1:20 (m:v) at 60 °C, during 6 h. A 10 kDa polysulfone hollow fiber membrane was used for the purification of the extract in different filtration modes, namely concentration and diafiltration, and a combination of both modes. Permeate fluxes and rejection rates were evaluated at different transmembrane pressure (TMP) at the shear rate of 10,187 s–1, at 40 °C. In concentration mode, increasing the volume reduction factor up to 6.1 led to a significant increase in the retention rates of acid-soluble lignin (ASL) and xylan, and a decrease in inorganic salt content in the retentate. In diafiltration mode, after 2.9 diavolumes, the acid-insoluble lignin (AIL) and xylan rejection rates drastically increased, as did the rejection rates of ash.